Hubungan Higiene Sanitasi dan Perilaku Penjamah Makanan dengan Kualitas Bakteriologis Peralatan Makan di Warung Makan - Chairini Tri Cahyaningsih, Haripurnomo Kushadiwijaya, Abu Tholib (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Eating utensils have crucial role in the hygiene and sanitation of foods. One among health requirements of eating utensils is that they do not contain bacteria exceeding the limits of health requirements. One factor causing high germ rate of food utensils is the behavior of food handlers in washing eating utensils.Objective: To identify the association between hygiene and sanitation (dish washing facilities) and behavior of food handlers (hygienic behavior and washing methods) and bacteriological quality (germ rate and number of E. coli) of plates at food stalls in the area of Catur Tunggal, Depok,  Sleman.Method: This observational study used cross sectional design. Samples were 40 food stalls that used running water to wash eating utensils. Eating utensil directly in contact with foods must not contain germ rate higher than 100 cfu/m2 and the number of E. coli must be 0 cfu/cm2 . Data were obtained through interviews, observations, and laboratory tests. Data analysis used Spearman Rank correlation test and multiple regressions. Result: There was an association between washing hands before working, washing hands without using soap after toileting, soaking, daily clean up and bacteriological quality with p<0.05. Education, wearing rings, keeping nails long, rinsing using running water, drying without using dish towel, sink made from strong and fine materials were not associated with bacteriological quality (p>0.05). The results of regression tests show that variables of soaking and daily clean up are closely related with bacteriological quality.Conclusion: There are significant associations between soaking and daily clean up and bacteriological qualityKeywords: sanitation hygiene, behavior of food handlers, bacteriological quality